La producción y pintura de máscaras de madera en los sectores, Latacunga, Salcedo, Pujilí, Saquisilí en el año 2023. - Ñacato Pila, Jonathan Javier (2023)
The research addresses the lack of recognition and support for wood and painting crafts in the cantons of Pujilí, Saquisilí, Salcedo, and Latacunga, located in the Cotopaxi province, Ecuador. These crafts, representing a rich cultural tradition and diversity in the region, have been marginalized due to the absence of a registration and sectorization system, negatively impacting their productivity and appreciation. The goal is to design a catalog that promotes and disseminates the sectorization of the production of these crafts, to preserve their cultural heritage and strengthen the community's identity. To gather the necessary information for the catalog, a qualitative descriptive research methodology was employed, using interviews to collect detailed information about artisanal production, and the cultural, historical, and symbolic aspects of these expressions. For the catalog design, Bruce Archer's 9 methodology was applied, ensuring an attractive and high-quality visual presentation. The significance of this project lies in valuing and preserving the region's rich artisanal tradition, enhancing cultural identity, and creating new opportunities for artisans and their families, who will be the direct beneficiaries. The introduction of the catalog will make it possible to promote products more successfully, reach new cantons, and blend traditions with those of other communities. Additionally, by encouraging sustainable tourism and enhancing its cultural richness, the project will indirectly help the province of Cotopaxi.